Biomarkers of oxidatively induced DNA damage in dreissenid mussels: A genotoxicity assessment tool for the Laurentian Great Lakes. Issue 9 (1st June 2017) - Jaruga, Pawel; Coskun, Erdem; Kimbrough, Kimani; Jacob, Annie; Johnson, W. Edward; Dizdaroglu, Miral
Abstract: Activities of fast growing human population are altering freshwater ecosystems, endangering their inhabitants and public health. Organic and trace compounds have a high potential for adverse impacts on aquatic organisms in some Great Lakes tributaries. Toxic compounds in tissues of organisms living in contaminated environments change their metabolism and alter cellular components. We measured oxidatively induced DNA damage in the soft tissues of dreissenid mussels to check on the possible contaminant‐induced impact on their DNA. The animals were obtained from archived samples of the National Oceanic and Atmospheric Administration (NOAA) Mussel Watch Program. Mussels were collected from the harbor of Ashtabula River in Ohio, and a reference area located at the Lake Erie shore. Using gas chromatography‐tandem mass spectrometry with isotope dilution, we identified and quantified numerous oxidatively modified DNA bases and 8, 5′‐cyclopurine‐2′‐deoxynucleosides. We found significant differences in the concentrations of these potentially mutagenic and/or lethal lesions in the DNA of mussels from the harbor as compared to the animals collected at the reference site. These results align NOAA's data showing that elevated concentrations of polycyclic aromatic hydrocarbons (PAHs), polychlorinated biphenyls (PCBs), and heavy metals were found in mussels within the harbor as compared to mussels collected in the reference site. The measured DNA lesions can be used as biomarkers for identifying DNA damage in mussels from polluted and reference sites. Such biomarkers are needed to identify the bioeffects of contaminants in affected organisms, as well as whether remedial actions have proven successful in reducing observed toxic effects.